Advancing sustainable agriculture: the role of integrated soil-crop management in maize production - Wang, Zhan; Zhao, Xiaoxiao; Sun, Yongfeng; Liu, Wei; Zhao, Guoqiang; Dang, Zhaohui (Frontiers in Environmental Science, 2024)
Objective: This study aims to evaluate the effectiveness of Integrated Soil-Crop System Management (ISSM) and provide technical support for sustainable high yield and efficiency in regional agriculture.The study compared the effects of no fertilization (Control), conventional farmer practices (FP), high-yield management (HY), and ISSM on maize yield and plant nutrient uptake.Measurements included grain yield, plant biomass, plant nutrient absorption, and soil nutrient content across different management strategies.Results: Over the 12-year experimental period, a significant decline in grain yield was observed under the Control treatment, with a slight decrease in the FP treatment. In contrast, consistent yield increases were noted for the HY and ISSM treatments. The ISSM approach significantly enhanced the average yield and plant uptake of P and K by 26%, 24%, and 32%, respectively, approaching 98%, 91%, and 85% of the levels achieved in the HY treatment. Furthermore, the average use efficiency of P and K fertilizers in the ISSM treatment exceeded those in the FP treatment by 18.7% and 1.2%, respectively, and those in the HY treatment by 17.4% and 24.8%, respectively. The adoption of ISSM led to a significant increase in total and available P and K content within the 0-20 cm and 20-40 cm soil layers and enhanced the available P and K content across all aggregate size fractions within the 0-20 cm soil layer.ISSM is capable of achieving long-term high and stable yields for spring maize, enhancing the uptake and utilization of P and K in plants, and bolstering the soil's capacity to supply these nutrients, thereby fostering the sustainable development of the entire soil-crop system.